Capparis Spinosa L. promotes anti-inflammatory response in vitro through the control of cytokine gene expression in human peripheral blood mononuclear cells - Moutia, Mouna (BMC Immunol, 2016)
BACKGROUND: Capparis Spinosa L. is an aromatic plant growing wild in dry regions around the Mediterranean basin. Capparis Spinosa was shown to possess several properties such as antioxidant, antifungal, and anti-hepatotoxic actions. In this work, we aimed to evaluate immunomodulatory properties of Capparis Spinosa leaf extracts in vitro on human peripheral blood mononuclear cells (PBMCs) from healthy individuals. RESULTS: Using MTT assay, we identified a range of Capparis Spinosa doses, which were not toxic. Unexpectedly, we found out that Capparis Spinosa aqueous fraction exhibited an increase in cell metabolic activity, even though similar doses did not affect cell proliferation as shown by CFSE. Interestingly, Capparis Spinosa aqueous fraction appeared to induce an overall anti-inflammatory response through significant inhibition of IL-17 and induction of IL-4 gene expression when PBMCs were treated with the non toxic doses of 100 and/or 500 μg/ml. Phytoscreening analysis of the used Capparis Spinosa preparations showed that these contain tannins; sterols, alkaloids; polyphenols and flavonoids. Surprisingly, quantification assays showed that our Capparis Spinosa preparation contains low amounts of polyphenols relative to Capparis Spinosa used in other studies. This Capparis Spinosa also appeared to act as a weaker scavenging free radical agent as evidenced by DPPH radical scavenging test. Finally, polyphenolic compounds including catechin, caffeic acid, syringic acid, rutin and ferulic acid were identified by HPLC, in the Capparis spinosa preparation. CONCLUSION: Altogether, these findings suggest that our Capparis Spinosa preparation contains interesting compounds, which could be used to suppress IL-17 and to enhance IL-4 gene expression in certain inflammatory situations. Other studies are underway in order to identify the compound(s) underlying this effect. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12865-016-0164-x) contains supplementary material, which is available to authorized users.